The German-Czech border region after the fall of the Iron Curtain: Effects on the labour market. An empirical study using the IAB Employment Sample (IABS) - Michael Moritz; Margit Gröger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
Using the IAB Employment Sample (IABS) covering 1980-2001 we investigate what impact the fall of the Iron Curtain has had on the skill structure of employment and wages in the western German districts neighbouring the Czech Republic. The introduction of free trade in this region, which has one of the world's largest spatial wage differentials, can be seen as a natural experiment. We presume that changes in skill and wage structures are particularly apparent in the regions situated immediately on the open border. Distinguishing three skill categories we obtain unexpected results. Though we observe a general shift from low-skilled jobs towards skilled jobs and a convergence trend of border regions towards the national average, we do not find a special effect for the period after the opening of the border, neither concerning the skill structure nor the wage differentials.
Keywords: R23; J31; F16; 330; Grenzgebiet; Qualifikationsstruktur; Lohnhöhe; osteuropäischer Transformationsprozess - Auswirkungen; IAB-Beschäftigtenstichprobe; Bayern; Tschechische Republik; Bundesrepublik Deutschland; Grenzgebiet; Internationale Wirtschaftsbeziehungen; Qualifikation; Lohnstruktur; Beschäftigungseffekt; Bayern (Ost); Tschechische Republik; Deutschland